The contribution of tropical long-term studies to mycology - Stallman, Jeffery K; Haelewaters, Danny; Koch Bach, Rachel A; Brann, Mia; Fatemi, Samira; Gomez-Zapata, Paula; Husbands, Dillon R; Jumbam, Blaise; Kaishian, Patricia J; Moffitt, Ariana; Catherine Aime, M (IMA fungus, 2024)
Fungi are arguably the most diverse eukaryotic kingdom of organisms in terms of number of estimated species, trophic and life history strategies, and their functions in ecosystems. However, our knowledge of fungi is limited due to a distributional bias; the vast majority of available data on fungi have been compiled from non-tropical regions. Far less is known about fungi from tropical regions, with the bulk of these data being temporally limited surveys for fungal species diversity. Long-term studies (LTS), or repeated sampling from the same region over extended periods, are necessary to fully capture the extent of species diversity in a region, but LTS of fungi from tropical regions are almost non-existent. In this paper, we discuss the contributions of LTS of fungi in tropical regions to alpha diversity, ecological and functional diversity, biogeography, hypothesis testing, and conservation-with an emphasis on an ongoing tropical LTS in the Pakaraima Mountains of Guyana. We show how these contributions refine our understanding of Fungi. We also show that public data repositories such as NCBI, IUCN, and iNaturalist contain less information on tropical fungi compared to non-tropical fungi, and that these discrepancies are more pronounced in fungi than in plants and animals.
Keywords: Biogeography; Conservation; Guiana shield; Taxonomy; Citizen science; Biodiversity; Endemic fungi